2(x-2)+3x=6x+7-(x-3)

Simple and best practice solution for 2(x-2)+3x=6x+7-(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-2)+3x=6x+7-(x-3) equation:


Simplifying
2(x + -2) + 3x = 6x + 7 + -1(x + -3)

Reorder the terms:
2(-2 + x) + 3x = 6x + 7 + -1(x + -3)
(-2 * 2 + x * 2) + 3x = 6x + 7 + -1(x + -3)
(-4 + 2x) + 3x = 6x + 7 + -1(x + -3)

Combine like terms: 2x + 3x = 5x
-4 + 5x = 6x + 7 + -1(x + -3)

Reorder the terms:
-4 + 5x = 6x + 7 + -1(-3 + x)
-4 + 5x = 6x + 7 + (-3 * -1 + x * -1)
-4 + 5x = 6x + 7 + (3 + -1x)

Reorder the terms:
-4 + 5x = 7 + 3 + 6x + -1x

Combine like terms: 7 + 3 = 10
-4 + 5x = 10 + 6x + -1x

Combine like terms: 6x + -1x = 5x
-4 + 5x = 10 + 5x

Add '-5x' to each side of the equation.
-4 + 5x + -5x = 10 + 5x + -5x

Combine like terms: 5x + -5x = 0
-4 + 0 = 10 + 5x + -5x
-4 = 10 + 5x + -5x

Combine like terms: 5x + -5x = 0
-4 = 10 + 0
-4 = 10

Solving
-4 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 15x-220=5x-10 | | 16-11x+12=-16x | | -2x-7+3x=2(5x-9) | | 3e/(e^x) | | 159*200000/X=8.50 | | 2-55m-5=73 | | 32x+48=11-x-7 | | 2(3x-5)=2x-1 | | (2n+6)(4n+2)+16=80 | | 2n^2-40=-11n | | 8n+1=13+2n+8n | | V^2-2vf+f^2=0 | | 3=7cos(2x) | | 3-18x-6=3 | | y=7cos(2x) | | 175+2(100)= | | 9x-124=3x-10 | | 3(2x+5)+3x=42 | | 5(3x-4)-6x=4x+8 | | (7t+6)+(3t+x)+(4t+y)=48 | | t^3+6t-4t-24=0 | | 175.00+3.00x=630 | | X^2-64i^2=0 | | 4+3lnx=17 | | 3p^2-4=p | | 4+3onx=17 | | y/55=11/7 | | 7z-2=3z+8 | | 20x^2+45=0 | | -5(3s-6)+16(s-5)=-54-4 | | 2x=1/3=5 | | 2m+12=0 |

Equations solver categories